+0  
 
0
77
1
avatar

g(x)=f(x)+p

g(x)=f(x+s)

assuming p and s are the same value

Guest May 16, 2017

Best Answer 

 #1
avatar+4155 
+2

No...for example let's say f(x) = x2

And...if p and s are the same, let's just call them both "p" .

 

First scenario:

g(x) = f(x) + p

g(x) = x2 + p

 

Second scenario:

g(x) = f(x + p)

g(x) = (x + p)2

g(x) = (x + p)(x + p)

g(x) = x2 + 2px + p2

 

f(x) + p  ≠  f(x + p)

 

If f(x) = x, then yes they turn out the same.

But they are not always equal.

hectictar  May 16, 2017
Sort: 

1+0 Answers

 #1
avatar+4155 
+2
Best Answer

No...for example let's say f(x) = x2

And...if p and s are the same, let's just call them both "p" .

 

First scenario:

g(x) = f(x) + p

g(x) = x2 + p

 

Second scenario:

g(x) = f(x + p)

g(x) = (x + p)2

g(x) = (x + p)(x + p)

g(x) = x2 + 2px + p2

 

f(x) + p  ≠  f(x + p)

 

If f(x) = x, then yes they turn out the same.

But they are not always equal.

hectictar  May 16, 2017

6 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details